2022
DOI: 10.1136/bmjopen-2022-061426
|View full text |Cite
|
Sign up to set email alerts
|

Troponin and short-term mortality in hospitalised patients with COVID-19 infection: a retrospective study in an inner-city London hospital

Abstract: ObjectiveTo investigate the association between troponin positivity in patients hospitalised with COVID-19 and increased mortality in the short term.SettingHomerton University Hospital, an inner-city district general hospital in East London.DesignA single-centre retrospective observational study.ParticipantsAll adults admitted with swab-proven RT-PCR COVID-19 to Homerton University Hospital from 4 February 2020 to 30 April 2020 (n=402).Outcome measuresWe analysed demographic and biochemical data collected from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In this study, patients with elevated vs normal troponin levels had similar rates of non-fatal complications, despite exhibiting significant differences in mortality rates. This observation appears similar to some other studies [20,41]. The cause of mortality in COVID-19 patients is often multi-factorial and remains incompletely understood [39].…”
Section: Plos Onesupporting
confidence: 91%
“…In this study, patients with elevated vs normal troponin levels had similar rates of non-fatal complications, despite exhibiting significant differences in mortality rates. This observation appears similar to some other studies [20,41]. The cause of mortality in COVID-19 patients is often multi-factorial and remains incompletely understood [39].…”
Section: Plos Onesupporting
confidence: 91%
“…A study by Shyam-Sundar et al [9] showed a relationship between troponin and mortality in COVID-19 cases. In another study of 2716 COVID-19 cases conducted by Case et al, [10] in-hospital mortality was found to be higher in patients with elevated troponin levels (12.2%; p<0.001).…”
Section: Discussionmentioning
confidence: 97%
“…Noteworthy, patients with cardiac injury were older, had more comorbidities such as hypertension, diabetes, coronary heart disease, and chronic heart failure, higher levels of CRP, TPI, N-terminal pro-B-type natriuretic peptide, and Cr, and had higher mortality than those without cardiac injury (51.2% vs 4.5%) [ 22 , 23 ]. Sundar et al also supported that patients with elevated levels were older, had more comorbidities such as ischaemic heart disease, heart failure, chronic kidney disease, higher white cell count, and consequently had higher in-hospital mortality (53.2% vs 19.0%) and death following readmission (3.2% vs 0.0%) than non-elevated patients [ 24 ]. Lyu and coworkers showed that patients with cardiac injury had higher age, history of heart failure, blood urea nitrogen (BUN) and Cr levels, and higher in-hospital mortality than the no cardiac injury group [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ayad and coworkers reported that the levels of TPI, D-dimer, CRP, and WBCs were remarkably higher in COVID-19 patients who died during hospitalisation than survivors [ 26 ]. Similarly, lung disease, age, TPI positivity, and continuous positive airway pressure ventilation were meaningfully associated with in-hospital mortality in COVID-19 patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%